Fatal Septicaemia Following Suprapubic Cystostomy in a Paraplegic Patient: Never Do a Cystostomy without Prior Urine Culture and Appropriate Antibiogram!. (7th June 2010) - Vaidyanathan, Subramanian; Soni, Bakul M.; Oo, Tun; Hughes, Peter L.; Singh, Gurpreet
Abstract : Neuropathic urinary bladder is often colonised by multidrug-resistant bacteria. We report a 64-year-old male spinal cord injury patient with paraplegia, who received gentamicin on empirical basis before undergoing suprapubic cystostomy, as antibiotic sensitivity report of urine was not available. This patient developed fulminate septicaemia. Although appropriate antibiotic therapy (meropenem) was started when this patient manifested features of sepsis, acute renal failure occurred and he expired. Inappropriate initial antimicrobial therapy was the major contributory factor for this patient's mortality. Learning points from this case are (1) never do a cystostomy without prior urine culture and appropriate antibiogram; (2) in a chronic spinal cord injury patient, full blood count, liver function tests, albumin level, and albumin to globulin ratio should be performed before any surgical procedure.